2009
DOI: 10.1089/jmf.2008.1127
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Vaccinium uliginosum L. Extract and Its Active Components

Abstract: Vaccinium uliginosum L. (also known as bog bilberry) is a low-growing deciduous shrub classified in the Ericaceae family of plants, which includes numerous Vaccinium berries, blueberries, and cranberries. Berries of the Ericaceae family are known to contain organic acids, vitamins, glycosides, and anthocyanins and have been reported to have antioxidant activity. In order to identify the antioxidative principles of V. uliginosum, we separated water extracts into polyphenol, anthocyanin-rich (pigment), and sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 22 publications
(27 reference statements)
0
15
0
1
Order By: Relevance
“…The crude extract and fractions containing polyphenol and pigment exhibited the greatest antioxidant activities with 50 % inhibitory concentration IC(50) values of 85.8, 33.2, and 16.7 lg/mL, respectively, for the DPPH assay, and 48.1, 83.8, and 51.9 lg/mL for the nonenzymatic superoxide radical assay. In our case, the highest antioxidant capacity was shown in water; therefore, for binding properties were used only these extracts [34]. The amount of total phenolics, anthocyanins, and ascorbic acid varied in berries depending on their maturity and varieties.…”
Section: Discussionmentioning
confidence: 98%
“…The crude extract and fractions containing polyphenol and pigment exhibited the greatest antioxidant activities with 50 % inhibitory concentration IC(50) values of 85.8, 33.2, and 16.7 lg/mL, respectively, for the DPPH assay, and 48.1, 83.8, and 51.9 lg/mL for the nonenzymatic superoxide radical assay. In our case, the highest antioxidant capacity was shown in water; therefore, for binding properties were used only these extracts [34]. The amount of total phenolics, anthocyanins, and ascorbic acid varied in berries depending on their maturity and varieties.…”
Section: Discussionmentioning
confidence: 98%
“…Vaccinium uliginosum L . (VU), known as bog bilberry, has been reported to have antioxidant and protective effects against VU-induced skin photoaging [3, 4]. A previous study showed that the berries have an anti-inflammatory effect [5].…”
Section: Introductionmentioning
confidence: 99%
“…Their results, based on thin-layer chromatographic comparisons with authentic standards, showed that this family is rich in fl avonoids and simple phenolics. Since then, due to the advancement of analytical instrumentation, a large number of analytical methods have been published on phenolic contents of individual Ericaceae plant species (Swaroop et al, 2005;Pawlowska et al, 2006;Burdulis et al, 2009;Kim et al, 2009). However, studies focusing on applying a single HPLC-UV-MS method to relatively larger number of Ericaceae plants are nonexisting.…”
Section: Introductionmentioning
confidence: 99%